Parasitosis intestinal en pacientes infectados con el virus de inmunodeficiencia humana - Cermeño Julman; Hernández Isabel; Uzcátegui Orlando; Páez Javier; Rivera Mario; Baliachi Norka (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2004)
Abstract: Patients infected with the Human Immunodeficiency Virus (HIV) often are diagnosed with gastrointestinal disease. We have determined the prevalence of intestinal parasites in HIV seropositive patients from the University Hospital Complex Ruiz y Paez in Bolivar, Venezuela. A study was designed to analyze faeces samples from 35 HIV infected individuals in a 12 months period. Three serial samples were analyzed using (i) direct exam, (ii) concentration methods (i.e., Formol-Ether sedimentation and Willis and Harada-Mori flotation), (iii) tricromic Kinyoun staining for Microsporidium and (iv) direct immunofluorescent. The most frequent parasites found in the faeces of HIV infected individuals were: Blastocystis hominis (85.7%), Entamoeba coli (77.1%) and Endolinax nana (37.1%). In addition, Cryptosporidium parvum was found in 7 AIDS patients, Cyclospora cayetanensis in 3 individuals (two of them with AIDS), and Microsporidium spp in 4 patients (11.4%). Interestingly, a statistically significant correlation between diarrhea and the presence of Coccidian and Microsporidium spp, was observed (p < 0.05). Finally, the most frequent helmints found in HIV infected patients were Ascaris lumbricoides (14.3%), hookworms and Trichuris trichiura (5.7%), while the only cestode found was Hymenolepis diminuta (5.7%). Intestinal parasites are frequently detected in HIV- infected patients from Bolivar State in Venezuela. Resumen: Los pacientes infectados con el Virus de Inmunodeficiencia Humana (VIH) padecen trastornos gastrointestinales. El objetivo de este estudio fue determinar la prevalencia de parásitos intestinales en individuos infectados por el VIH en el Complejo Hospitalario Universitario "Ruiz y Páez", estado Bolívar, Venezuela; donde no existían estudios previos. Se obtuvieron muestras de heces de pacientes con diagnóstico confirmado de infección por el VIH en un período de 12 meses. Se estudiaron tres muestras seriadas realizando examen directo y métodos de concentración: sedimentación por Formol-Éter, flotación de Willis y Harada-Mori. Además, tinción de Kinyoun, Tricrómica para Microsporidium y observación de la muestra mediante fluorescencia directa. Fueron diagnosticados: Blastocystis hominis (85,7%), Entamoeba coli (77,1%) y Endolinax nana (37,1%). Cryptosporidium parvum se demostró en 7 pacientes con SIDA; Cyclospora cayetanensis en 3 pacientes, 2 de los cuales padecían el SIDA y Microsporidium spp en 4 pacientes (11,4%). Hubo asociación estadísticamente significativa entre diarrea y la presencia de Coccidios y Microsporidium spp (p<0,05). Los helmintos demostrados fueron: Ascaris lumbricoides (14,3%), Ancylostomideos y Trichuris trichiura (5,7%). El único céstodo fue Hymenolepis diminuta (5,7%). Las parasitosis intestinales son frecuentes en pacientes infectados con VIH en el estado Bolívar, siendo la blastocistosis y las infecciones por coccidios las prevalentes.